PERAN WANITA BEKERJA SERTA PELATIHAN KETERAMPILAN DALAM RUMAH TANGGA SEBAGAI KESETARAAN GENDER DI KOTA PALANGKA RAYA - Rita Yuanita Toendan; Peridawaty Peridawaty (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to increase public understanding of the role of women working and the importance of household skills training as a form of strengthening gender equality in Palangka Raya City. Gender equality is not only interpreted as equal rights between men and women, but also as an effort to provide equal access, opportunity, participation, control, and benefits in family, work, education, economy, and social life. Working women have a strategic role in supporting the family economy, improving household welfare, and contributing to regional development. However, women still face challenges in the form of double burdens, limited access to skills, and unbalanced division of household roles. Based on BPS data, the Participation Rate of the female labor force in Palangka Raya City in 2024 is 49.37 percent, while the male is 82.15 percent. This data shows that there is still a gap in economic participation between men and women. This activity is carried out through counseling, discussion, practical skills training, and mentoring. The results of the activity showed that participants gained an increased understanding of gender equality, the importance of division of roles in households, and productive skills that can be developed into household businesses. This activity is expected to strengthen the role of women in the family and society and encourage the creation of fairer gender relations in Palangka Raya City.